2020
DOI: 10.1039/c9ra03736e
|View full text |Cite
|
Sign up to set email alerts
|

A porcine acellular dermal matrix induces human fibroblasts to secrete hyaluronic acid by activating JAK2/STAT3 signalling

Abstract: By activating the JAK2/STAT3 pathway, 3D-GF-PADM induces the production of hyaluronic acid in human fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Additionally, skin barrier function and hydration are affected by Src/AKT/NF-κB and MAPK signaling [34,35]. The proximal promoter of HAS2 has transcription factor-binding sites for the JAK2/STAT3 pathway [36]. Rauhala et al found that the active purinergic P2Y2 receptor largely promotes HAS2 expression and several signaling pathways are associated with HAS2 regulation, such as Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), calcium-activated PKC, calcium response element-binding protein (CREB), and MAP kinase cascades [28].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, skin barrier function and hydration are affected by Src/AKT/NF-κB and MAPK signaling [34,35]. The proximal promoter of HAS2 has transcription factor-binding sites for the JAK2/STAT3 pathway [36]. Rauhala et al found that the active purinergic P2Y2 receptor largely promotes HAS2 expression and several signaling pathways are associated with HAS2 regulation, such as Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), calcium-activated PKC, calcium response element-binding protein (CREB), and MAP kinase cascades [28].…”
Section: Discussionmentioning
confidence: 99%
“…ECM has been known as an essential member of myocardial healing following ischemic injury and a crucial mediator for cell regeneration and endogenous tissue reconstruction [24][25][26]. Natural acellular tissue 3D cell culture systems have attracted increasing interest in tissue engineering due to better simulating the microenvironment where in vivo cells grow [27][28][29][30][31][32]. This study investigated the growth, proliferation, and angiogenesis signaling pathway in cardiomyocytes derived from isoproterenol-induced MI and healthy mice cultured on the acellular aortic matrix (3D system) and compared them with healthy and injured cells cultured in a 2D system.…”
Section: Discussionmentioning
confidence: 99%
“…Hst1 was dissolved in 1 ml 0.9% NaCl and supplemented with Hst1 formulations at final concentrations of 1, 10, and 50 μM. The ADM (Jiangsu Unitrump Biomedical Technology Co., Ltd., Nanjing, China) is an enzymatically digested product in a form of ultrafine powder with an average particle size at 33.4 μm ( Liu and Sun, 2020 ). Before application, ADM powder was mixed with different concentrations of Hst1 at a volume ratio of 1:1 (v/v) through three-way pipes for 1 h, forming into pastes.…”
Section: Methodsmentioning
confidence: 99%